DEVELOPMENTAL STATE OF SOCIAL PARTNERSHIP AT THE KHMELNYTSKY CENTER FOR VOCATIONAL EDUCATION AND TRAINING IN SERVICE SECTOR (Innovative professional education, 2023)
The state of development of social partnership on the example of the activities of the State Educational Institution «Khmelnytskyi Center for Vocational Education in the Service Sector» is analyzed. The conclusion is made about the effectiveness of cooperation between the vocational (vocational-technical) education institution and social partners with the aim of developing information and methodological materials, updating the material and technical base, etc.
Keywords: vocational education and training (VET), social partnership, cooperation, effectiveness of social partnership